The Anthropocene in Antarctica. Considering "fixed" and "more fluid" perspectives of analysis - Zarankin, Andrés; Salerno, Melisa Anabella
Starting in 1995, our research project seeks to learn more about human presence in Antarctica; in particular, though not exclusively, about sealers´ encounters with the South Shetland Islands in the nineteenth century. In this chapter we discuss the material dimension of the Anthropocene in Antarctica from an archaeological point of view. First, we describe our initial approaches to the subject, when we were still constrained by an orthodox understanding of the material world. Second, we critically reflect on our previous work and explore new possibilities for analysis, considering a challenging definition of the material world, bodily experience, and the interconnectedness of the webs of life. Fil: Zarankin, Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina. Universidade Federal Do Minas Gerais. Departamento de Sociología y Antropología; Brasil Fil: Salerno, Melisa Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina